A apropriação do pensamento epistemológico de Ernst Mach por Freud e Skinner - Elias, Liana Rosa (2012)
This attends to clarify the appropriation of epistemological thinking of Ernst Mach (1838-1916) by Sigmund Freud (1856-1939) and Burrhus Frederic Skinner (1904-1990). Similarities and distinctions were found in this respect, by which Abib called pre-text in its epistemological method. The categories that served to machians analysis were: (1) monism of sensations, (2) the role of subjectivity in science, (3) definition of science and scientific explanation by Mach. Wheras the agnosticist foundation that Freud gave to Metapsychology, it was found the appropriation perteins sometimes to relationship between science and philosophy, sometimes to the boundaries of science as an dynamic and open knowledge. The Mach’s referees in Skinner were: the functional relations in his scientific explanation, the criticism of the mechanical explanations, the adoption of a monism; and, the object, objectives and validity in science, beyond the adoption of Mach’s descriptivism as an explanation in science. Regarding the appropriations alluded to, the following similarities were found between Freud and Skinner: Machian’s conception that science is a human activity in pursuit of functional relations, the transient character of scientific explanation, and no relation to the sensational phenomenism. Regarding differences in the appropriations, it was found that the Skinner alluded more widely to the Mach’s proposes to science, while Freud, beyond this, considered models of physicalism and energetismo, what Assoun called rational realism; what combined a Machian’s phenomenalism and an operational rationalism. Skinner maintained the principles of adequacy of thoughts to facts and the role of hypotheses according to Mach, but were beyond; also conceived interpretation as a means of production of scientific knowledge. Here’s another distinction founded: Skinner structured its theory on the functional relations model and the anti-metaphysical critique adopted by Mach, while Freud considers the arguments of the energestism’s critics. It was found, finally, that despite its appropriations on the Mach’s epistemological view, both Freud and Skinner created novel concepts in their science.